2020
DOI: 10.7150/ijms.39367
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin: A promising tool or just another overhyped test?

Abstract: Sepsis is the leading cause of death worldwide. Timely administration of antibiotics is recognized as the cornerstone in the management of sepsis. However, inappropriate use of antibiotics may lead to adverse effects and the selection of drug-resistant pathogens. Microbiological cultures remain the gold standard to diagnose infection despite their low sensitivity and the intrinsic delay to obtain the results. Certain biomarkers have the benefit of rapid turnover, potentially providing an advantage in timely di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 72 publications
0
29
0
2
Order By: Relevance
“…However, the optimal use of PCT-guided antibiotic therapy has been discussed for a long time [ 19 , 20 ]. Many reviews and meta-analyses concluded that PCT is a good indicator of bacterial infection [ 21–24 ] and that overall antibiotics exposure can be reduced safely [ 25–36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal use of PCT-guided antibiotic therapy has been discussed for a long time [ 19 , 20 ]. Many reviews and meta-analyses concluded that PCT is a good indicator of bacterial infection [ 21–24 ] and that overall antibiotics exposure can be reduced safely [ 25–36 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCT levels increase in bacterial infections from an extrathyroidal origin and rise early in course of infection, therefore making it useful biomarker for decision making regarding initiation of antibiotic therapy as results of blood culture are not available immediately. 15 One hundred and twenty six blood specimens of critically ill patients admitted with suspicion of sepsis in intensive care unit were analyzed for PCT, CRP, TLC and lactate and compared with blood culture results as gold standard for bacterial infection. Majority of patients with positive blood culture were male (73%).…”
Section: Discussionmentioning
confidence: 99%
“…When there is bacterial infection, various tissues outside the thyroid can be induced to express calcitonin I, leading to PCT being released into the blood in large quantities (9). The process is divided into 2 phases: the first is the early phase (2-3 h after infection), which is mainly caused by bacterial infection itself or endotoxin stimulation; and the latter is the delayed phase, which is mainly caused by inflammatory factors (such as TNF-α, IL-1, IL-2, IL-6) which initiate a large amount of synthesis and release of PCT in various tissues outside the thyroid (10). The delayed phase is also an important reason for the peak of PCT within 12-24 h after systemic bacterial infection (11).…”
Section: Discussionmentioning
confidence: 99%